New species of Compsocidae (Insecta, Psocodea) from Cretaceous Burmese amber - Sroka, Pavel; Nel, André (Zootaxa, 2017)
A new fossil species of the family Compsocidae, namely Burmacompsocus coniugans sp. nov. is described from Late Cretaceous Burmese amber. Diagnostic characters separating the new species from the previously known representatives of the genus are discussed. Details of mouthparts and genitalia are described for the genus for the first time. The discovery of the new species supports the hypothesis of higher Compsocidae diversity existing in the past compared with the present.